Students as Knowledge Mediators in Transnational Higher Education (International Journal of Multidisciplinary Perspectives in Higher Education, 2020)
This study aims to gain a deeper understanding of knowledge transfer as an outcome of transnational education. Based on the case of a Finnish–Vietnamese transnational education program, this paper analyzes the role of students as knowledge mediators between the study program, students’ personal development and work life. Although students should play a critical part in learning and transferring knowledge between study and work life in theory, it seems that in practice, their role might be rather limited and passive. While multiple external factors affect learning and knowledge transfer, students’ prior knowledge, skills and experience were found to be more significant factors, which teachers and program designers should carefully consider while promoting stronger participation. This paper contributes to the discussion on transnational higher education by elaborating students’ changing role as knowledge transferors and transferees and by bringing the students’ voice to the debate on the outcomes and impacts of transnational higher education.